Pelatihan Vocational Ekspor Impor Produk UKM Bersama di Sentani, Jayapura - Sri Handoko Sakti; Rimi Gusliana Mais; Maya Mustika; Munir Munir; Muhammad Ikhsan; Engkur Engkur (PROGRESIF: Jurnal Pengabdian Komunitas Pendidikan, 2023)
This article describes the implementation of vocational training in the export-import sector where the material is more focused on exports for small and medium-sized businesses who want to increase their practical knowledge in the fields mentioned above. The practical knowledge that will be given to participants is from how participants as potential exporters are given knowledge including how to start an import-export business, knowledge about products and finding markets for export destination countries, preparing export documents, and finally how to process for sending theirs export goods. For the learning is in the form of a seminar with direct face to face between the participants and the facilitator. As for the learning method, the emphasis is on practical knowledge rather than theoretical knowledge, as well as cases and providing many opportunities for participants to tell about the products to be exported, preparations and what obstacles were experienced by participants in starting their exports. That way participants will better understand the process and procedures directly. The expected result of this vocational training is that participants not only gain adequate knowledge of export and import but also directly practice it on the products they have produced in order to be able to export to the markets of the targeted countries. As for maximizing the achievement of these targets, the Ministry of Cooperatives must facilitate a process of mentoring participants either directly, for example by forming a group of similar business groups accompanied by a facilitator, or indirectly, namely by forming a whats-up group or providing zoom facilities in communicating and consulting. Key Words: Export import, Facilitator, learning methode, target achievment.